Захист акустооптичного каналу витоку інформації при застосуванні зловмисником лазерної системи акустичної розвідки - Гребенчук, М. В. (ХНУРЕ, 2024)
This work is devoted to protection against remote listening of acoustic in formation with the help of laser intelligence tools. The intelligence system described below has already been used in practice both in large-scale operations against terrorist organizations and in internal intelligence of some countries. At the beginning of 2022, the threat of organizing terrorist acts, preparations for wars and attacks between different countries has increased significantly, it is necessary to take countermeasures and use all possible means of intelligence to save the lives of civilians. This system of acoustic intelligence can be useful for state special services. However, it is worth knowing how to avoid it and how to prevent information leakage through the acousto-optic information channel.
Keywords: захист акустооптичного каналу; канал витоку інформації